Hippocampal Subcellular Organelle Proteomic Alteration of Copper-Treated Mice. (30th March 2018) - Yu, Haitao; Jiang, Xin; Lin, Xuemei; Zhang, Zaijun; Wu, Desheng; Zhou, Li; Liu, Jianjun; Yang, Xifei
Abstract: Copper neurotoxicity has been implicated in multiple neurological diseases. However, there is a lack of deep understanding on copper neurotoxicity, especially for low-dose copper exposure. In this study, we investigated the effects of chronic, low-dose copper treatment (0.13 ppm copper chloride in drinking water) on hippocampal mitochondrial and nuclear proteome in mice by 2-dimensional fluorescence difference gel electrophoresis coupled with MALDI-TOF-MS/MS. Behavioral tests revealed that low-dose copper caused spatial memory impairment, DNA oxidative damage as well as loss of synaptic proteins. Proteomic analysis revealed modulation of 31 hippocampal mitochondrial proteins (15 increased and 16 decreased), and 46 hippocampal nuclear proteins (18 increased and 28 decreased) in copper-treated versus untreated mice. Bioinformatic analysis indicated that these differentially expressed proteins are mainly involved energy metabolism (NDUV1, COX5B, IDH3A, and PGAM1), synapses (complexin-2, synapsin-2), DNA damage (PDIA3), apoptosis (GRP75), and oxidative stress (SODC, PRDX3). Among these differentially expressed proteins, synapsin-2, a synaptic-related protein, was found to be significantly decreased as confirmed by Western-blot analysis. In addition, we found that superoxide dismutase [Cu-Zn] (SODC), a copper ion target protein, was identified to be decreased in copper-treated mice versus untreated mice. We also found that stathmin (STMN1), a microtubule-destabilizing neuroprotein, was significantly decreased in hippocampal nuclei of copper-treated mice versus untreated mice. Taken together, we conclude that low-dose copper exposure causes spatial memory impairment and perturbs multiple biological/pathogenic processes by dysregulating the mitochondrial and nuclear proteome, particularly the proteins related to respiratory chain, synaptic vesicle fusion, axonal/neurtic integrity, and oxidative stress. The change of STMN1 and SODC may represent early novel biomarkers of copper neurotoxicity.